2013
DOI: 10.2139/ssrn.2357953
|View full text |Cite
|
Sign up to set email alerts
|

The Factors that Influenced Consumptive Behavior: A Survey of University Students in Jakarta

Aldo Enrico,
Ritchie Aron,
Weriyen Oktavia

Abstract: Abstract-Nowadays, in big cities the consumptive behaviors among university students become common. However this fact indicates a negative impact for financial performance because students have not found their money yet. This journal is conducted with a purpose, to know what the factors that affect people's consumptive behavior are. This research journal is conducted in Jakarta, Indonesia, and the respondents are students from several universities that are located in Jakarta. The method that we are using is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 4 publications
2
11
0
11
Order By: Relevance
“…Impulsive buying behavior is one of the most popular research topics among the consumer researchers today to address the causes, driving forces and triggers of impulsive buying behavior. This reality is reinforced by the era in which we live now, and shopping has been identified as a form of recreational activity (Enrico et al, 2014). Through the internet, the opportunity of purchases for consumer has been expanded through increased accessibility for products and services to increase the convenience in making purchases.…”
Section: Introductionmentioning
confidence: 99%
“…Impulsive buying behavior is one of the most popular research topics among the consumer researchers today to address the causes, driving forces and triggers of impulsive buying behavior. This reality is reinforced by the era in which we live now, and shopping has been identified as a form of recreational activity (Enrico et al, 2014). Through the internet, the opportunity of purchases for consumer has been expanded through increased accessibility for products and services to increase the convenience in making purchases.…”
Section: Introductionmentioning
confidence: 99%
“…So, here attitude also influences the consumption. Lifestyle was also in the middle category that influences consumption Furthermore, by Enrico & Oktavia (2014) have found that prestige is also factor that influences consumptive behavior. Prestige is one of important thing for some people.…”
Section: Factors That Cause Of Consumptive Behaviormentioning
confidence: 99%
“…Consumptive behaviour is one behaviour that can not be separated from the daily life of society. Enrico, et al (2014) argues that the emergence of consumptive behaviour knows no national borders, in which Indonesia is included. The facts show that most Indonesian people behave consumptively and love new goods, and are willing to spend some of their income to buy new products that are a trend (Pratama, 2013).…”
Section: Consumptive Behaviourmentioning
confidence: 99%